Improving natural product research translation: From source to clinical trial. Issue 1 (10th December 2019) - Sorkin, Barbara C.; Kuszak, Adam J.; Bloss, Gregory; Fukagawa, Naomi K.; Hoffman, Freddie Ann; Jafari, Mahtab; Barrett, Bruce; Brown, Paula N.; Bushman, Frederic D.; Casper, Steven J.; Chilton, Floyd H.; Coffey, Christopher S.; et al.
Abstract: While great interest in health effects of natural product (NP) including dietary supplements and foods persists, promising preclinical NP research is not consistently translating into actionable clinical trial (CT) outcomes. Generally considered the gold standard for assessing safety and efficacy, CTs, especially phase III CTs, are costly and require rigorous planning to optimize the value of the information obtained. More effective bridging from NP research to CT was the goal of a September, 2018 transdisciplinary workshop . Participants emphasized that replicability and likelihood of successful translation depend on rigor in experimental design, interpretation, and reporting across the continuum of NP research. Discussions spanned good practices for NP characterization and quality control; use and interpretation of models (computational through in vivo) with strong clinical predictive validity; controls for experimental artefacts, especially for in vitro interrogation of bioactivity and mechanisms of action; rigorous assessment and interpretation of prior research; transparency in all reporting; and prioritization of research questions. Natural product clinical trials prioritized based on rigorous, convergent supporting data and current public health needs are most likely to be informative and ultimately affect public health. Thoughtful, coordinated implementation of these practices should enhance the knowledge gained from future NP research.